2020
DOI: 10.3390/w12082160
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Estimation Using Citizen Observatory Data, Microwave Satellite Imagery, and Environmental Covariates

Abstract: Soil moisture (SM) is a key variable in the climate system and a key parameter in earth surface processes. This study aimed to test the citizen observatory (CO) data to develop a method to estimate surface SM distribution using Sentinel-1B C-band Synthetic Aperture Radar (SAR) and Landsat 8 data; acquired between January 2019 and June 2019. An agricultural region of Tard in western Hungary was chosen as the study area. In situ soil moisture measurements in the uppermost 10 cm were carried out in 36 test fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…A study by Sanuade et al (2020) revealed that the SVM model was most suited for the study area situated within the University of Ibadan campus in Nigeria; these results are markedly better than what is achieved in the current study; however, the improved estimation may have been enabled by a smaller catchment area and a denser sampling network (i.e., 75 sampling points in 0.0253 km 2 ). The GLM displayed a good performance compared to Kibirige and Dobos (2020), who used an MLR approach. While the error metrics obtained for the current study are satisfactory and share commonalities with the previous literature, the comparison is difficult given the vastly different catchment land uses, areas, and climatic conditions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A study by Sanuade et al (2020) revealed that the SVM model was most suited for the study area situated within the University of Ibadan campus in Nigeria; these results are markedly better than what is achieved in the current study; however, the improved estimation may have been enabled by a smaller catchment area and a denser sampling network (i.e., 75 sampling points in 0.0253 km 2 ). The GLM displayed a good performance compared to Kibirige and Dobos (2020), who used an MLR approach. While the error metrics obtained for the current study are satisfactory and share commonalities with the previous literature, the comparison is difficult given the vastly different catchment land uses, areas, and climatic conditions.…”
Section: Discussionmentioning
confidence: 93%
“…The aspect (Figure 5) is the cardinal direction a slope faces. This is an important parameter as it influ-ences the terrain's exposure to sunlight, thus forming variable microclimate regions across neighboring slopes (Kibirige & Dobos, 2020). For instance, north-facing slopes often receive less exposure to sunlight, and therefore more moisture can be observed owing to a cooler microclimate.…”
Section: Terrain Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study utilised a microwave backscatter model to compute the groundwater content. The data is accessible on the European Space Agency (ESA) website (https://scihub.copernicus.eu/provided) (Asmuß et al 2018;Kibirige and Dobos 2020). The data used (refer to Table 1) are obtained from the Sentinel-1A C-band SAR image, which records backscatter signals day and night, regardless of lighting and weather conditions.…”
Section: Satellite Datamentioning
confidence: 99%
“…This high density elevation point data can be interpolated or converted to any raster datasets of 1 meter scale raster resolution. This DEM can later be used to model the surface and subsurface water flow and nutrient translocation within the field, and it is also a very efficient predictor for digital soil mapping approaches [8][9][10][11][12][13][14]. Plant condition characterization is using proximal and remote sensing datasets and produce vegetation indices and other indirect information to describe the biomass and the crop "wellness" around the field.…”
Section: Introductionmentioning
confidence: 99%